Ulrich Beck and the sociological paradigm of risk - Jacondino, Eduardo Nunes; Eslabão, Daniel da Rosa (FCL-UNESP Laboratório Editorial, 2015)
This article develops theoretical-conceptual analysis about the sociological paradigm of risk, as presented by the eminent German sociologist, contemporary and recently deceased, Ulrich Beck. Through it we seek to establish some conceptual distinctions, related to traditional approach predominant in social sciences with regarding social observation; as well as t establish a dialogue with theoreticians who also converge on this topic. We wish, finally, to contribute to the understanding of the paradigmatic society risk proposition, which converges to fruitful discussions vis-à-vis the horizons of reflexivity and contemporary sciencesociety dialogue, so indispensable in the face of the new historical moment lived in the present.some conceptual distinctions, related to traditional approach predominant in socialsciences with regarding social observation; as well as t establish a dialogue withtheoreticians who also converge on this topic. We wish, finally, to contribute to theunderstanding of the paradigmatic society risk proposition, which converges tofruitful discussions vis-à-vis the horizons of reflexivity and contemporary sciencesocietydialogue, so indispensable in the face of the new historical moment lived inthe present.